Multi-level human resource development and the mediating role of business strategy in non-financial business performance: Evidence from Vietnamese enterprises - Ngô Bá, Thành; Phạm Thế, Anh; Nguyễn Thị Hồng , Đào (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
This study examines the impact of multi-level human resource development on firms’ non-financial business performance through the mediating role of business strategy. Data were collected from 343 managers and middle-level employees across Vietnamese enterprises. The partial least squares - structural equation modeling (PLS-SEM) approach was employed to test the research model and hypotheses. The results reveal that multi-level human resource development positively and indirectly influences non-financial business performance via business strategy; thereby elucidating how human resource capabilities are transformed into non-financial outcomes such as customer satisfaction, innovation capability, and corporate reputation. The study extends the resource-based view (RBV) and dynamic capabilities theories within the context of an emerging economy, offering both theoretical and managerial implications for integrating human resource development into strategic management practices to enhance sustainable non-financial performance.